Musculoskeletal complaints, work posture, and vibration exposure among bag-sewing artisans - Dakwatun Shofia; Shofiyah Nur Rosydah; Ragil Ismi Hartanti; Noeroel Widajati (Malahayati International Journal of Nursing and Health Science, 2026)
Background: Craft workers are particularly vulnerable to developing Musculoskeletal Disorders (MSDs), with reported prevalence ranging from 38.5% to 100%, including among bag artisans. MSDs are influenced by individual factors, work-related factors, and environmental conditions. The Tanggulangin area is well known as a center for the bag and suitcase industry and was identified as a population at risk based on preliminary observations. Purpose: To describe individual factors, work-related factors, vibration exposure, and complaints of Musculoskeletal Disorders (MSDs) among bag artisans. Method: This study employed a descriptive analytical design with a cross-sectional study. A total of 38 bag artisans participated in the study. Data were collected using the Rapid Entire Body Assessment (REBA) questionnaire to assess work posture, the Nordic Body Map (NBM) questionnaire to evaluate MSD complaints, and a vibration meter to measure vibration exposure. Results: The findings indicated a tendency for smoking habits (OR = 1.123) and awkward working posture (OR = 1.500) to be associated with MSD complaints. Meanwhile, environmental exposure in the form of vibration intensity did not exceed the established Threshold Limit Value (TLV). Conclusion: No statistically significant associations were identified between the examined individual or occupational factors and MSD complaints. All measured vibration exposures were below the applicable threshold limit, preventing comparison between different exposure levels.